RELIGIOUS EXTREMISM AS A FORM OF INTERNATIONAL ORGANIZED CRIME IN THE NORTHERN CAUCASUS - IARALIEV, Imam (CENTRAL ASIA AND THE CAUCASUS, 2004)
During the last decade the law enforcement bodies of the Northern Caucasus have been confronted with a new problem: religious extermism as part of international terrorism. A careful analysis of its causes shows that in the Soviet past, when the state borders remained under strict control and were virtually closed to all types of criminals from other countries, no criminal elements could penetrate the autonomous North Caucasian republics. After the Soviet Union fell apart into new independent states, after economic and social-political reforms were launched in the 1990s, and after Russia began to lose its foothold in the Northern Caucasus, the local republics were caught in the midst of all kinds of interregional and international criminal organizations, including terrorist groups. Daghestan was their most attractive target, probably because of its geopolitical situation (Russia’s southern border and unstable neighbors—Georgia, Azerbaijan, and the Chechen Republic, its long Caspian coastline, rich natural resources ranging from oil and gas to uranium ores and a very specific infrastructure), and the Europe-Caucasus-Asia transportation routes. Today, the republic’s operational structures have registered over 150 organized criminal groups, 20 of them connected with similar groups abroad, while 6 or 8 of them are purely terrorist organizations. The latter are engaged in all types of terror: social-political (assassination of prominent public and political figures—they have al-ready murdered the minister of finance, the head of the ministry of national relations, and several deputies of different levels), nationalist (confrontations between ethnic groups accompanied by felonies), religious (clashes between the Wahhabis and common Muslims, assassination of a mufti),and criminal (contracted murders, criminal wars,abductions, etc.). The republican law enforcement bodies intercepted several coups and attempts to seize the building housing the State Council and the republic’s government. Under Soviet power, terrorism was described as a product of Western ideology; the nation was told that the FBI and CIA were engaged in training international terrorists; one Soviet author went as far as including the U.S. police academies on this list. This suited the ruling party. Today, we are well aware of the real situation and know what produc-es terrorism, who supplies it with ideological pil-lars, and who pays for it. We also know where ter-rorists are trained. In Russia, so-called religious extremism is the most dangerous manifestation of international ter-rorism; it unites criminals and other law offenders under the slogan of establishing an Islamic republic in Daghestan. In fact, to achieve their own po-litical and mercenary aims, they are trying to im-pose the alien ideology of Wahhabism and the idea of struggle for so-called pure Islam on the North Caucasian peoples. It should be said that neither religious extremism, nor Islamic terrorism, nor Wahhabism have anything in common with true Islam: this world religion rejects violence and the use of force. These terms are applied to crimes com-mitted under the banner of religion. According to the Russian special services, Wahhabism came to the Northern Caucasus in the early 1990s when active and open propaganda of this religious trend was launched in some of the regions. The Wahhabis opened their mosques, published and distributed their reactionary writings free of charge, and set up illegal armed detachments allegedly to defend Islamic values. According to the Committee for Religious Affairs in the government of Daghestan, in 1992-1996 foreign sponsors (international Islamic organizations) spent about 1m to build about 40 and renovate 16 mosques and 5 madrasahs in the republic.